Israeli national security policy : political actors and perspectives - Reich, Bernard; Kieval, Gershon R. (New York Greenwood Press, 1988)
What sets this book apart is its focus not simply upon the twin strategic imperatives underlying Israeli security policy but also its attention to the interplay amongst the key domestic actors involved in formulating Israeli attitudes concerning national security. . . <a class="q ruhjFe NJLBac fl" href="https://books.google.com/books/about/Israeli_National_Security_Policy.html?id=uVIsAAAAYAAJ&source=kp_book_description" data-ved="2ahUKEwiZgoL9y6brAhWO-6QKHRqrAzsQmhMwDnoECAoQAg">Google Books​
1. Israeli National security policy: issues and actors/ Bernard Reich-- 2. The foreign policy of the labor party/ Gershon R. Kieval -- 3. The foreign policy of herut and the likud/ Ilan Peleg -- 4. The ethnic factor in Israel’s foreign policy/ Maurice M. Roumani -- 5. The Religious parties and Israel’s foreign policy/ Stewart Riser -- 6. Extremist inputs into Israel’s foreign policy: the case of Gush Emunim/ Ehud Sprinzak -- 7. Tehiya as a permanent nationalist phenomenon/ Aaron D. Rosenbaum -- 8. Israeli public opinion on peace issues/ Gloria H. Falk -- 9. Coping with turbulence: the first tow years of the nationl unity government under peres/ Marver H. Bernstein
​Includes index Bibliography p.: 225-230
Keywords: Military science; MILITARY POLICY; GOVERNMENT POLICY; ISRAEL